Military Justice Institutions of the USSR in the 1930s – 1950s: the Soviet and Russian Historiography - KODINTSEV, Aleksandr Yakovlevich; SHKAREVSKY, Denis Nikolaevich (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The authors of this article analyze institutions of the Soviet military justice system presented in both Soviet and Russian historiography. The main objective is to compare historiographical concepts of the Soviet and modern periods in connection with military tribunals. The study uses the comparative-historical method. Throughout the research, the authors have concluded that the historiography under consideration can be divided into two periods. The first lasted until the early 1990s, and the second one started in the 1990s and continues to this day. Most studies conducted in the first and the second periods are too descriptive. Scholars mainly list institutions of the Soviet judicial system. They do not consider grounds for the formation of these institutions or the factors that caused their later reforms. However, Soviet scholars describe in detail the facade of the judicial system, while post-Soviet scientists are able to document their observations in a free form. At the same time, the latter form two groups. The first group of researchers still believes Soviet courts were well organized and functioned effectively. The second group holds to an opinion that Soviet courts were an instrument of repression